(untitled) (Research, Society and Development, 2024)
Introduction: congenital diaphragmatic hernia (CHD) is a pathology that is presented by an alteration in the diaphragm that favors the passage of abdominal organs to the chest, causing difficulty in the normal development of the lungs and, consequently, in many cases, pulmonary hypoplasia and pulmonary hypertension as the main clinic. In more severe situations of the clinic there is the possibility of performing intrauterine surgery called fetal Endoscopic tracheal occlusion (fetus) in order to assist the development closer to the physiological of the lungs and thus improve the prognosis. Results and discussion: the best diagnostic method is ultrasound during prenatal care. This follow-up is essential, for a possible intrauterine intervention, if necessary, such as HDC. Objective: to make an approach on the HDC, taking into account the etiopathogenesis of the disease, the most appropriate imaging method for diagnosis, its treatment and possible complications. Materials and methods: an integrative review of the literature containing the most recent studies, from 2019 to 2024, related to the theme was carried out through research in the LILACS and MedLine databases, through the VHL portal. Conclusion: the prognosis of HDC is favorable due to advances in imaging methods such as ultrasound, tomography and magnetic resonance imaging, since the good accuracy of these methods allow early diagnosis, in addition to detecting abnormalities and the level of severity. In addition, extrinsic factors such as maternal age is a prognostic factor to be evaluated, since it has a great impact on the evolution and prognosis of the case.